(untitled) (Biocenosis, 2022)
The Environmental Education Master Plan for Costa Rica was a project devised by Mario Boza and Alvaro Ugalde (considered the fathers of the National Parks of this country). It was formulated in the years 1987-88, from the Neotropical Foundation and with the support of the Mac Arthur Foundation of the United States. It was the first effort in the country with specific funding to promote Environmental Education at all levels. The work plan included various stages in order to obtain the necessary information for the formulation of the action plan. There was government support, through the creation by executive decree of a National Commission for Environmental Education, in charge of promoting its execution by the corresponding instances.